2023
DOI: 10.1001/jamanetworkopen.2023.9981
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Disclosure of Disability and Request for Accommodations Among First-Year Resident Physicians in the US

Abstract: ImportanceEnsuring access to accommodations is critical for resident physicians and their patients. Studies show that a large proportion of medical trainees with disabilities do not request needed accommodations; however, drivers of nonrequests are unknown.ObjectiveTo assess the frequency of accommodation requests among first-year resident physicians (ie, interns) with disabilities and to identify possible drivers of nonrequest for needed accommodations.Design, Setting, and ParticipantsAs part of the Intern He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Access to accommodations have shown to improve burnout metrics among students with disabilities . Fear of stigma and lack of clear institutional processes are substantial barriers to disability disclosure and requesting accommodations . Limitations of this study include our inability to cluster results by medical school and to examine prevalence of multiple disabilities and burnout across other demographic groups, including sexual and/or gender minority and socioeconomic status .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Access to accommodations have shown to improve burnout metrics among students with disabilities . Fear of stigma and lack of clear institutional processes are substantial barriers to disability disclosure and requesting accommodations . Limitations of this study include our inability to cluster results by medical school and to examine prevalence of multiple disabilities and burnout across other demographic groups, including sexual and/or gender minority and socioeconomic status .…”
Section: Discussionmentioning
confidence: 96%
“… 2 Fear of stigma and lack of clear institutional processes are substantial barriers to disability disclosure and requesting accommodations. 5 Limitations of this study include our inability to cluster results by medical school and to examine prevalence of multiple disabilities and burnout across other demographic groups, including sexual and/or gender minority 2 and socioeconomic status. 6 This study highlights the necessity to address burnout among Asian and URiM students with multiple disabilities through applying critical intersectional, antiracist, and antiableist lenses to promote equity in medical training.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the number of students with disabilities matriculating into medical schools and mitigating barriers through reasonable accommodation(s) are essential commitments by medical associations and obstetrics and gynecology (Ob/Gyn) medical education committees toward realizing the goal of a diverse physician workforce 2,3 . Despite these commitments, the number of medical students with mobility disabilities, including wheelchair users, remains low 4,5 …”
mentioning
confidence: 99%
“…2,3 Despite these commitments, the number of medical students with mobility disabilities, including wheelchair users, remains low. 4,5 In 2021, 5.9% of MD-granting medical school students reported a disability, a significant increase from 2019 (4.6%) and 2015 (2.8%), 5 whereas a 2020 study identified that 4.27% of osteopathic (DO) students reported a disability. 4 These findings highlight the dearth of disability representation in medical education, specifically the small proportion of students with mobility disabilities in MD (2.6% in 2015, 3.5% in 2019, and 3.2% in 2021) 5 and DO (4.5% in 2020) programs.…”
mentioning
confidence: 99%
See 1 more Smart Citation